Предмет: Математика,
автор: Andrei9721
x(7+3)-4x = 8x+17+36-5x
3x(7+5)+6x-34=5x+3x-4x+36+21
Ответы
Автор ответа:
0
1) х(7+3)-4х=8х+17+36-5х
7х+3х-4х=8х+17+36-5х
6х=3х+53
6х-3х=53
3х=53
х=53:3
3х(7+5)+6х-34=5х+3х-4х+36+21
21х+15х+6х=4х+57
42х=4х+57
42х-4х=57
38х=57
х=57:38
х=1,5
7х+3х-4х=8х+17+36-5х
6х=3х+53
6х-3х=53
3х=53
х=53:3
3х(7+5)+6х-34=5х+3х-4х+36+21
21х+15х+6х=4х+57
42х=4х+57
42х-4х=57
38х=57
х=57:38
х=1,5
Похожие вопросы
Предмет: Другие предметы,
автор: 888Ananasik888
Предмет: Химия,
автор: blanshulya
Предмет: Русский язык,
автор: aisanasikibaeva
Предмет: История,
автор: Kapitolinaqd
Предмет: Алгебра,
автор: wwwmolchan1985